The Energy-Economic Growth Nexus in Indonesia (Journal of Business Management and Accounting, 2017)
The aim of this study is to investigate the causal relationship between final energy consumption and economic growth for three main development sectors in Indonesia. In this study, we consider final energy consumption as energy indicator and the value added of development sectors as economic indicator. We use annual data from 1971 to 2014 and collected data from international energy agency and the world development indicator. We use Autoregressive distributed lag (ARDL) technique for cointegration and granger causality approach to explore direction of causality between the variables. We found a bidirectional relationship between energy and economic growth in the industrial sector in the long-run and in services sector in the short-run. Furthermore, we found a unidirectional relationship from economic growth to energy consumption in the services sector in the long-term and in the agriculture sector in the short and long terms. Based on these results, we concluded that economic growth is significantly influenced by final energy consumption on three development sectors in Indonesia, especially in the long-term. However, this study only focus on exploring energy-economic growth nexus on three development sectors in Indonesia and provide specific information for the policy makers on the three sectors in Indonesia. This study provides a new approach in terms of exploring energy-economic growth nexus in a single country and assess that energy-economic growth nexus in a single country should consider situations and conditions in each development sector.